Pressões institucionais na divulgação dos capitais do relato integrado - Silva, David Stanhy de Carvalho (2017)
The disclosure of organizational performance gets new directions in conjecturing the proposal of integrating information from financial and non-financial reports in an one report that satisfies the information needs of stakeholders. In this perspective, the partnership between the Global Reporting Initiative (GRI) and the Prince's Accounting for Sustainability Project (A4S) arose in 2010 to create the International Integrated Reporting Council (IIRC) to foment a corporate report that shows value creation by organizations, the Integrated Reporting, that communicates in a clear, concise and integrated way the process of creation of value in the short, medium and long term through six capitals: Financial, Manufactured, Intellectual, Human, Social and Relationship, and Natural. In the context of Institutional Theory, the New Institutionalism and the National Business Systems Approach explain the increasing economic integration with its effects on organizational forms and management practices, and both have in common the focus on the adaptation of organizations in institutional environments. Through New Institutionalism, it can be observed three isomorphic forces that lead organizations to become increasingly similar: coercive pressures, mimetic pressures, and normative pressures, while the National Business Systems Approach addresses national differences across countries through of four key characteristics: political system, financial system, education and labor system, and cultural system. This research has objective to analyze the disclosure of the Capitals proposed by the International Integrated Reporting Framework from the perspective of New Institutionalism and the National Business Systems Approach in 30 companies of the IIRC Pilot Programme located in Brazil, Netherlands and United Kingdom. The methodology is characterized as exploratory, documentary and qualitative-quantitative, using analysis of the content, analysis of variance (ANOVA) and analysis of panel data. The results demonstrate a low level of disclosure of reporting capital by companies, but companies located in Brazil and the Netherlands report more than companies located in the United Kingdom. Considering the classification of social and environmental risk, it was verified that companies classified with elevated risk divulge more than companies classified with minimal risk. Finally, the dissemination of the Integrated Reporting is pressured by the normative and mimetic isomorphism of New Institutionalism in the sample of this study.